THE CONFIDENCE OF THE YOUTH, THE FOUNDATION OF OUR FUTURE- OUR CONSTITUTION (Ta'limning zamonaviy transformatsiyasi, 2024)
To raise the nation to the nation, the state to the state level and even the whole country, to join the ranks of the world conditions, to create a peaceful life for the future generation of our country, in a word, in any case, we have the rights of every individual. Changes are being made to our basic accounting constitution in the coming days. Through three articles, you are also a child, at least partially, of the news introduced into our constitution.